COMMUNICATION EFFECTIVENESS AND IMAGE OF THE NATIONAL AGENCY FOR DISASTER MANAGEMENT (BNPB) IN DISSEMINATING COVID-19 INFORMATION IN INDONESIA - Nikmatus Sholikah; Saza Azizah Anindyo (OISAA, 2022)
Indonesia is a country that has a fairly high positive number of COVID-19 in the Asian continent. In the context of dealing with the virus, this study aims to examine the effectiveness of the government's public relations performance in delivering messages on handling COVID-19 through BNPB Instagram, namely @bnpb_indonesia and images from BNPB. We use the Social Network Analysis (SNA) analysis method which measures the degree of centrality, closeness centrality and betweenness centrality. This type of descriptive qualitative research and data collection techniques used is the questionnaire method and involves 112 respondents spread across several regions in Indonesia. The results of our research conducted in April 2020 show that BNPB through the @bnpb_indonesia Instagram account has a good image. This can be seen from the survey conducted showing that 92.9% knew about the BNPB instagram, BNPB's performance and completeness of information was ranked first out of 14 other reference instagram accounts regarding information related to COVID-19. Then the effectiveness of BNPB's communication through the @bnpb_indonesia instagram account is considered good, it can be seen from the mapping of networks on social media using the SNA method, the results of degree centrality or key actor @bnpb_Indonesia rank first of 14 information references. Then betweeness Centrality and Eigenvector or the most connected actor is the instagram node @bnpb_indonesia, which is ranked first.